Climate Resilience Indonesia's National Strategic Program for Social Justice as a Paradox of Coloniality - Nuchraha Alhuda Hasnda; David Pradhan; Satrio Wibowo (Jurnal Dinamika Hukum, 2025)
The National Strategic Projects (PSN) are designed to mitigate and adapt the impacts of climate change and safeguard essential environmental functions, due to emissions from the energy sector, the second-largest source of greenhouse gas (GHG) emissions after land-use change and forestry. The rhetoric of sustainable development underlying a colonial rationality that reproduces extractivist regimes, the dispossession of Indigenous territories, and the subordination of local communities in favor of national elites and global markets. Law functions not as a protector of community rights but as a tool to legitimize green grabbing in the name of climate crisis mitigation. This study critically examines the climate law politics of Indonesia in framing National Strategic Projects as solutions for social justice. The research addresses how the coloniality of power operates within national climate law and explores how policy directions can be transformed toward decolonial climate justice grounded in self-determination. Methods used are an interdisciplinary socio-legal approach , global political ecology, and critical coloniality studies. The research analyzes the role of law in structuring and normalizing resource extraction under the narratives of energy transition. The main instrument is a critical legal-political analysis of climate resilience, focusing on legal frameworks, state-corporate actors, and the exclusion of local communities. The result of this research identifies practices of coloniality; power, being, and etymology, and the need for decolonial approaches to climate resilience. The recommendations are local needs-based policies that prioritize affected communities, self-determination through meaningful participation in planning and implementation, and corrective justice as a mechanism to review legal policies for adaptation, restore social rights, and ensure egalitarian knowledge.